Structural reliability analysis and prediction - Melchers, Robert E.; Beck, Andre T. (New Jersey: Wiley, 2018)
Structural Reliability Analysis and Prediction, third Edition is a textbook which addresses the important issue of predicting the safety of structures at the design stage and also the safety of existing, perhaps deteriorating structures. Attention is focused on the development and definition of limit states such as serviceability and ultimate strength, the definition of failure and the various models which might be used to describe strength and loading. This book emphasises concepts and applications, built up from basic principles and avoids undue mathematical rigour. It presents an accessible and unified account of the theory and techniques for the analysis of the reliability of engineering structures using probability theory. This new edition has been updated to cover new developments and applications and a new chapter is included which covers structural optimization in the context of reliability analysis. New examples and end of chapter problems are also now included.
Measures of structural reliability -- Structural reliability assessment -- Integration and simulation methods -- Second-moment and transformation methods -- Reliability of structural systems -- Time-dependent reliability -- Load and load effect modelling -- Resistance modelling -- Cods and structural reliability -- Probabilistic evaluation of existing Structures -- Structural optimization and reliability -- Summary of probability theory -- Rosenblatt and other transformations -- Bivariate and multivariate normal integrals -- Complementary standard normal table -- Random numbers -- Selected problems
Includes bibliography and index
Keywords: Structural Stability; Reliability (Engineering); Probabilities